PELATIHAN DAN PERAWATAN KENDARAAN RODA EMPAT NEGLA UNTUK MENINGKATKAN KUALITAS PELAYANAN NEGLA SARI TANGERANG - Wilshen Wilshen (Jurnal Abdi Mandala, 2023)
The car repair business does not only rely on car maintenance service activities, but is supported by comfortable facilities and excellent service. The "Koh Aloy" car repair shop is a micro-small business with a number of limitations, including limitations on the types of service services, infrastructure facilities, sources of funds, and the ability to manage a repair shop. The objectives of this training include car service with injection technology, application of a workshop administration system and management of the Occupational Health and Safety Environment (LK3). The target subjects of the activity are workshop managers and mechanics. Evaluation of training participant satisfaction is carried outthrough customer satisfaction measurement instruments. The results of the training and mentoring activities for small and micro car repair shops in Negla Sari Tangerang to increase the competitiveness of this service are; 1) the service activities carried out at the "Koh Aloy" Car Repair Shop, received a pretty good response. The indicators are that both the manager and the mechanics of the partner car repair shop participate in the activity from start to finish; 2) training and mentoring activities for car repair shop managers and mechanics, have increased knowledge about injection technology and service for injection technology cars, entrepreneurship and marketing management, workshop administration systems, recording financial reports, and environmental management, occupational safety and health (LK3 ); and 3) training and mentoring activities have provided provisions for car repair shop managers and mechanics to be better prepared in providing injection car service services.